On the war-episodes in Hikayat Kuda Semirang Sira Panji Pandai Rupa - Koster, Gijs L. (Wacana, Journal of the Humanities of Indonesia, 2020)
This paper, based on the text of the Jakarta MS C. St. 125 published by Lukman Ali and M.S. Hutagalung (1996), shows by a comparative reading of selected samples of war-episodes in the hikayat, that, in spite of the countless differences between them, all ultimately tell one and the same underlying story. This story is in each war-episode retold in a process of constant variation within identity. This is done by combining “pre-fab” units that each form a slot in an already predetermined narrative structure. Each of these slots is filled with a selection of type-scenes, made from the particular string of type-scenes that is available for that particular slot. In order to shed light on the question where the hikayat’s author may have found the models and inspiration for its composition, the numerous intertextual echoes of Javanese and Malay literary genres and individual works audible in these war-episodes are also traced.